Where's Mommy? - Donofrio, Beverly; McClintock, Barbara (New York : Schwartz & Wade Books, 2014)
While trying to keep their friendship a secret from their mothers, a human girl and a mouse make a surprising discovery.
Keywords: Friendship -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Mice -- Juvenile fiction